Results reporting in single case experiments and single case meta-analysis. (August 2018) - Vannest, Kimberly J.; Peltier, Corey; Haas, April
Highlights: Illustrations of statistical reporting in single case experimental design as complementary to visual analysis. Elaborates why explicit design justifications are important for improving the science. Introduces the idea that correspondence reporting between visual and statistical analysis is an issue of training, criteria, and a source of reliability. Abstract: Single Case Experimental Design is a discipline grounded in applied behavior analysis where the needs of individual clients and the application of scientific inquiry are fundamental tenets. These two principles remain tantamount in the conduct of research using this methodology and the expansion of the method into evidence-based practice determinations. Although recommendations for quality indicators are widespread, implementation is not. Concurrent to the rise of quality indicators is an increasing interest in analysis methodology. Visual analysis has a history of application and validity, newer forms of analysis less so. While some argue for concordance between the two, it may be the differences that are worth exploration in understanding characteristics of trend and variability in much of the published literature. Design choice and visual analysis decisions are rarely fully articulated. Statistical analyses are likewise inadequately justified or described. Recommendations for the explicit language of reporting as derived from prior meta-analysis and a current review of two leading journals provides a scaffold consistent with existing guidelines but additive in detail, exemplars, and justification. This is intended to improve reporting of results for individual studies and their potential use in future meta-analytic work.